Functional recovery priorities and community rehabilitation service preferences of spinal cord injury individuals and caregivers of Chinese ethnicity and cultural background - Lam, Chor Yin; Koljonen, Paul Aarne; Yip, Christopher Chun Hei; Su, Ivan Yuen Wang; Hu, Yong; Wong, Yat Wa; Cheung, Kenneth Man Chee (Frontiers in Neurology, 2022)
Introduction Spinal cord injury (SCI) causes significant and permanent disability affecting motor, sensory and autonomic functions. We conducted a survey on the priorities of functional recovery and preferences for community rehabilitation services in a cohort of Chinese individuals with SCI as well as the primary caregivers. The study also investigated their views on advanced technology and research. Methods An online platform with a self-administered questionnaire was used to collect the opinions of clients that received services from an SCI follow-up clinic, a self-help association, or a non-government organization from 1 September−31 December 2021. Results Eighty-seven subjects (74 individuals with SCI−48 tetraplegic, 26 paraplegic, and 13 caregivers) responded to the survey. Recovery of arm/hand function was given the highest priority among tetraplegics, followed by upper trunk/body strength and balance, and bladder/bowel function. Sexual function had a significant lower ranking than all priority areas except normal sensation (p < 0.05). Paraplegics viewed bladder/bowel function as the most important area of functional recovery, followed by walking movement, upper trunk/body strength and balance, elimination of chronic pain, and regaining normal sensation. There was no statistically significant difference among the top priority areas (p > 0.05). In contrast to previous studies done in Western populations, the study revealed that sexual function was ranked as the lowest by all 3 groups of respondents (tetraplegics, paraplegics, and caregivers). The majority of participants thought community rehabilitation services were inadequate. Most of the respondents were interested to try advanced technology which would facilitate their daily life and rehabilitation. About half of the individuals with SCI thought advance in technology and research could bring significant improvement in their quality of life in the coming 10 years. Conclusion This survey is the first study specifically looking into the recovery and rehabilitation priorities of a Chinese population of individuals with SCI. This is also the first study to investigate the priorities of the primary caregivers of SCI individuals. The findings are useful as a reference for planning of future research and provision of rehabilitation services for the SCI community locally and in other parts of China.